Long-Term Survival of Mycobacterium avium subsp. paratuberculosis in Fecal Samples Obtained from Naturally Infected Cows and Stored at −18°C and −70°C - Eran A. Raizman; L. A. Espejo; S. J. Wells (Veterinary Medicine International)
The objective was to evaluate the survival of Mycobacterium paratuberculosis (Map) in naturally infected dairy cows feces under long periods of freezing at −18°C and −70°C. Samples were collected from cows previously tested positive with serum ELISA or fecal culture, or with clinical signs of Johne's disease. Samples were stored at −18°C and/or −70°C and recultured in Herrold's egg yolk media every 3–6 months. A proportional odds mixed model was used for data analysis. Sixty nine fecal samples were stored for different periods between September 2002 and January 2005. Of these, 45 (65%) were stored at −18°C and 24 (35%) at −70°C. Average number of days between repeated culture dates was 98 and 84 for −18°C and −70°C, respectively. Median number of repeated cultures was 6 and 4 for samples stored at −18°C and −70°C, respectively. After adjusting for initial sample bacterial load, the effects of temperature or number of thawing and refreezing cycles on Map viability were not significant. The probability that a sample decreases from high to moderate-low bacterial load and from moderate-low to negative bacterial load was 13.5% per month. Although this study found gradual reduction of Map concentration in stored fecal samples through time, overall survival in −18°C can ease fecal samples management in laboratories with low-processing capacity or lack of −70°C freezer.